DESIGN & IMPLEMENTATION MARKER USING MEDIA FLASHCARDS FOR 10 SAMPLE TOGA PLANTS - Fardani Annisa Damastuti (NJCA (Nusantara Journal of Computers and Its Applications), 2018)
Augmented Reality (AR) is a technology with real-world concepts with dimensions of the world that can be revealed realtime. AR usually presented using a Smartphone platform that enables easy development of applications which appropriate, affordable and accessible to multiple users. Benefits of using AR can be used as an interactive educative learning in various fields. One of these areas is learning about family planning education (TOGA) among junior high school students with the struggle time 13-15 years. TOGA is a cultivated home crop that is efficacious as a medicine. Packed with Flashcards and media design combined with the latest technology to make students want to know and improve the science associated with TOGA. With the design of "Design And Implementation Marker With Flashcards Media For 10 Samples of TOGA", it is expected to create a more interactive learning environment that can be used directly with virtual world objects.